A trium test on beyond ΛCDM triggering parameters - Sakr, Ziad (Journal of cosmology and astroparticle physics, 2023)
We performed a Bayesian study on three beyond ΛCDM phenomenological triggering parameters, the growth index γ, the dark energy equation of state parameter ω and the lensing deviation from the GR prediction parameter Σ, using the latest cosmological geometric, growth and lensing probes, all in a consistent implementation within the modified gravity cosmological solver code MGCLASS. We find, when we combined all our probes, i.e. the cosmic microwave background (CMB), the baryonic acoustic oscilation (BAO), the growth measurements fσ 8 and the 3×2pt joint analysis of weak lensing and galaxy clustering in photometric redshift surveys, assuming flat space, constraints compatible with general relativity and ΛCDM with ω = -1.025 ± 0.045, and Σ = 0.992 ± 0.022 at the 68% level, while γ = 0.633±0.044 is still within ∼ 2σ from the ΛCDM value of γ ∼ 0.55, and that when Σ is considered as constant; while γℓ = -0.025 ±0.045 when the lensing parameter is parameterised as function of a lensing index, introduced for the first time in this work, as Σ(z) = Ωm(z)γℓ .